Histogenic differentiation of polar tuberculoid granuloma and the "benign" or "malignant" behaviour of hanseniasis - Jorge MICHALANY; Nílceo S. MICHALANY (Hansenologia Internationalis, 1989)
B a s e d o n a n ew mo r p h o l o g i c a l c o n c e p t a n d c l a s s i f i c a t i o n o f granulomatous inflammation: the polar granulomas, on the histogenesis of the tuberculoid granuloma of the posi t ive Mi tsuda test and on the relat ionship between the degree of histogenetic differentiation and behaviour of tumors, the Authors concluded that the "benign" or "malignant" behaviour of hanseniasis depends on the degree of tuberculoid differentiation of the lesions. If the lesion is histologically well differentiated toward a polar tuberculoid granuloma (tuberculoid hanseniasis) it will have a "benign" behaviour. On the contrary, if this differentiation is absent (virchowlan hanseniasis) or poor (interpolar bordeline hanseniasis) the behaviour of the lesion will be "malignant".